Un archéologue capucin en Éthiopie (1922-1936) : François Bernardin Azaïs - Amélie Chekroun (Afriques)
In 1922, the Capuchin monk François Bernardin Azaïs, a former missionary of the Province of Hārar between 1897 and 1913, was commissioned by the French government to realise some archaeological researches in Ethiopia. In total, he achieved ten archaeological and ethnological missions in the South and the East of the country. Only his first four expeditions are known today, thanks to his book Cinq Années de recherches archéologiques en Éthiopie (1931). During the other eleven years, Azaïs wrote numerous progress reports and articles, still unpublished and kept in the Capuchin archives in Roma. This new documentation will help the researcher to increase the knowledge about the archaeological sites of southern Ethiopia and the history of Ethiopian institutions like the National Library or the National Museum and an archaeological institute. We can say that Azaïs is the father of South Ethiopian archaeology.